2000
DOI: 10.1677/joe.0.1670331
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal growth factors and pancreatic islet hormones during postoperative IGF-I supplementation in man

Abstract: Insulin-like growth factor-I (IGF-I) has been demonstrated to exert a nitrogen sparing effect, both experimentally and in patients after abdominal surgery. IGF-I is a major mediator for the anabolic effects of growth hormone (GH). Whether elevated circulating IGF-I levels are the sole mediator of the anabolic effects following GH has not been clarified. IGF-I influences glucose metabolism, both through its own specific receptor and by activating the insulin receptor, and has also been proposed to influence pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In some studies IGF-1 given alone postoperatively showed no effect on nitrogen [26, 36]. IGF-1 treatment during 5 days postoperatively reduced plasma insulin and glucose levels, indicating an improved insulin sensitivity following surgery [35]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies IGF-1 given alone postoperatively showed no effect on nitrogen [26, 36]. IGF-1 treatment during 5 days postoperatively reduced plasma insulin and glucose levels, indicating an improved insulin sensitivity following surgery [35]. …”
Section: Discussionmentioning
confidence: 99%
“…In the present study a daily supply of GH (0.3 IU/kg/day) and IGF-1 (80  μ g/kg/day) was chosen since these amounts have shown effects on protein and substrate metabolism in earlier studies during the postoperative period [5, 11, 3135]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation